2013
DOI: 10.1111/pce.12076
|View full text |Cite
|
Sign up to set email alerts
|

Long‐distance abscisic acid signalling under different vertical soil moisture gradients depends on bulk root water potential and average soil water content in the root zone

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…4C) throughout the experiment suggests this is unlikely (although this response may differ in non-peat-based substrates). Alternatively, it seems more likely this is a root-derived response, which may have a number of potential explanations, including decreased synthesis of root ABA (Zhang and Tardieu 1996), decreased flux of ABA from the roots (Jokhan et al 1996) and variation in soil moisture distribution (Puertolas et al 2013) between the different irrigation treatments. Future work should focus on understanding why FDI attenuates the [X-ABA] leaf response.…”
Section: Discussionmentioning
confidence: 99%
“…4C) throughout the experiment suggests this is unlikely (although this response may differ in non-peat-based substrates). Alternatively, it seems more likely this is a root-derived response, which may have a number of potential explanations, including decreased synthesis of root ABA (Zhang and Tardieu 1996), decreased flux of ABA from the roots (Jokhan et al 1996) and variation in soil moisture distribution (Puertolas et al 2013) between the different irrigation treatments. Future work should focus on understanding why FDI attenuates the [X-ABA] leaf response.…”
Section: Discussionmentioning
confidence: 99%
“…The PRD irrigation strategy evolved from studies with potted grapevines where it was observed that water use efficiency could be increased without reducing berry size by alternating the wet and dry portions of the root zone to induce root-to-shoot signaling of abscisic acid (ABA) (Stoll, Loveys, & Dry, 2000). A consistent response to PRD can be induced under controlled conditions; however, under field conditions, vine response to PRD has frequently been undistinguishable from that of other deficit irrigation strategies and response has been found to vary according to the supplied percentage of ET c (Dodd, 2009;Davies et al, 2011;Sadras, 2009;Chaves et al, 2010;Puértolas, Alcobendas, Alarcón, & Dodd, 2013;Romero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the saturated water content in flooded wet samples, the presence of the soil moisture gradient and unfilled pores in the dry samples usually led to a heterogeneous environments with both anaerobic and aerobic micro niches (Puertolas et al 2013), which would support higher microbial diversities (Walsh et al 2005;Crump et al 2012). As a carrier of nutrients, the soil water also regulates the soil nutrients (Bao et al 2015), which were considered to be the best predictors of microbial diversity (Nielsen et al 2010;Wessén et al 2010).…”
Section: Archaeal Diversity Related To Water Floodingmentioning
confidence: 99%